2016
DOI: 10.1007/s10096-016-2805-7
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive detection and identification of bacterial DNA in the blood of patients with sepsis and healthy volunteers using next-generation sequencing method - the observation of DNAemia

Abstract: Blood is considered to be a sterile microenvironment, in which bacteria appear only periodically. Previously used methods allowed only for the detection of either viable bacteria with low sensitivity or selected species of bacteria. The Next-Generation Sequencing method (NGS) enables the identification of all bacteria in the sample with their taxonomic classification. We used NGS for the analysis of blood samples from healthy volunteers (n = 23) and patients with sepsis (n = 62) to check whether any bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
122
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(138 citation statements)
references
References 34 publications
(33 reference statements)
11
122
1
Order By: Relevance
“…Among the healthy volunteers, anaerobic bacteria accounted for the main proportion (76.2%) of bacterial species, and the abundance of Actinobacteria phyla was significantly higher than that in patients with sepsis (76.3% in healthy volunteers and 31.0% in the sepsis patients), while among the sepsis patients, most species (75.1%) were aerobic or microaerobic microorganisms, and the abundance of phyla in the Proteobacteria was significantly higher in patients with sepsis than in the healthy volunteers (16.4% in healthy volunteers and 60.1% in sepsis patients). 51 Grumaz et al 52 The specific technical problems in the diagnosis of pathogens by mNGS include the following. First, mNGS is limited to roughly judging the species of pathogenic microorganisms and estimating the approximate proportion of those microorganisms, and the results of different tests or from different labs may vary.…”
Section: Devices: Microbial Identification and Detection Of Antimicromentioning
confidence: 99%
“…Among the healthy volunteers, anaerobic bacteria accounted for the main proportion (76.2%) of bacterial species, and the abundance of Actinobacteria phyla was significantly higher than that in patients with sepsis (76.3% in healthy volunteers and 31.0% in the sepsis patients), while among the sepsis patients, most species (75.1%) were aerobic or microaerobic microorganisms, and the abundance of phyla in the Proteobacteria was significantly higher in patients with sepsis than in the healthy volunteers (16.4% in healthy volunteers and 60.1% in sepsis patients). 51 Grumaz et al 52 The specific technical problems in the diagnosis of pathogens by mNGS include the following. First, mNGS is limited to roughly judging the species of pathogenic microorganisms and estimating the approximate proportion of those microorganisms, and the results of different tests or from different labs may vary.…”
Section: Devices: Microbial Identification and Detection Of Antimicromentioning
confidence: 99%
“…On the bases of sampling 242 healthy adults at 18 different anatomical sites of the human body and sequencing the 16S rRNA genes the presence of 5177 microbial taxonomic profiles was proven, but only 800 of them could be cultured [1]. The observation of cell-free DNAemia is well described feature of the healthy blood [2] [3], but the presence of transient culturable blood microbiota in the blood of healthy individuals could also be supposed. We tested whether the presence of DNA in healthy blood is associated with DNAemia or it is due to existing blood microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Kalfin reported 100% positivity of the blood cultures. Subsequently several other authors questioned the existence of the blood microbiome or DNAemia in healthy individuals, Domingue (1977) [5], (1997) [7], Nikkari et al (2001) [8], Mc Laughlin et al (2002) [9], Moriyama et al (2008) [10], Markova (2015) [11], Damgaard (2015) [12] Dimova et al (2017) [13], Gosiewski et al (2017) [2] and Kowarsky et al (2017) [3]. The authors reported supporting electron microscopy, cultural and molecular data in favour of the existence of the blood microbiota in healthy individuals.…”
Section: Tedeschi Et Al Reported On Incorporation Of Nucleosides Inmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Classification of bacteria is the fundamental first step for bacterial taxonomy determination and is mainly based on the differences in cellular composition, cellular metabolism, and cellular structure.G enetic analysis approaches,such as PCR (polymerase chain reaction), [5] FISH (fluorescence in situ hybridization), [6] and NGS (next generation sequencing) [7,8] are powerful techniques for the identification of bacteria, but these are often inappropriate in clinical diagnosis and wastewater treatment, which require ar apid diagnosis and in situ monitoring, due to the heavy preparative work and the huge amount of data required for in-depth analysis . Gram staining has been the gold standard technique for bacterial classification based on the different physical properties of the bacterial cell-wall structure. [1][2][3][4] Classification of bacteria is the fundamental first step for bacterial taxonomy determination and is mainly based on the differences in cellular composition, cellular metabolism, and cellular structure.G enetic analysis approaches,such as PCR (polymerase chain reaction), [5] FISH (fluorescence in situ hybridization), [6] and NGS (next generation sequencing) [7,8] are powerful techniques for the identification of bacteria, but these are often inappropriate in clinical diagnosis and wastewater treatment, which require ar apid diagnosis and in situ monitoring, due to the heavy preparative work and the huge amount of data required for in-depth analysis . Gram staining has been the gold standard technique for bacterial classification based on the different physical properties of the bacterial cell-wall structure.…”
mentioning
confidence: 99%